Development of a Novel Software Interface for Tracking Student Behavior, Performance and Attendance - Todd, Charlie; Secco, Emanuele Lindo (Digital Technologies Research and Applications, 2025)
This paper presents a novel software interface for tracking student behavior, performance and attendance, exploring how software is used in education and analyzing the benefits and challenges that can come with its use. Technology has become increasingly important to education over recent years, making it a major focus within both technology and education. In this context, the paper presents the implementation of a website, designed to convey how technology can streamline access to information, making it faster and more efficient than the usual paper-based methods used to track attendance, behavior and grades of students. Leveraging on the Technology Acceptance Model (TAM) and the Constructivist Learning Theory (CLT), a Client-Application Server and Database have been integrated into a novel framework where different users (i.e., student, parent, teacher, admin) can query the database. Role-based access is controlled through users’ tables which contain the user ID, name, email, and password. The relationships between the tables are enforced using foreign keys to maintain data integrity. The proposed system’s design prioritizes accessibility, enhancing the learning capability with a user-friendly interface. The system’s performance has been successfully tested in terms of time response, speed, efficiency and clarity. Initial single-user testing showed a load time of 18 ms for the student login page, with further validation needed for multi-user scenarios.